Penjernihan Air Selokan Institut Teknologi Adhi Tama Surabaya - Nahara, Annisa Ridha (Institut Teknologi Adhi Tama Surabaya, 2023)
Clean water is water used for daily needs whose quality meets health requirements and can be drunk when it has been cooked. This clean water is obtained from dug wells, drilled wells, rain water, tap water, ground water, and water from springs. The purpose of this experiment is to reduce wastewater pollution by using aluminum sulfate as a coagulant by looking at various parameters including pH, odor, color and hardness. The pH and odor parameters did not change when alum was added. The color of the wastewater changes from bluish green to clear after adding alum and waiting 1×24 hours. To determine hardness, standardized EDTA solution with CaCO3, pH 10 buffer solution and EBT indicator are required to determine hardness. The concentration of EDTA used was 0.1 M with a total hardness of 660 ppm and 220 ppm before and after adding aluminum sulfate.